Lifetime Extension of DC-Link Capacitors in Three-Level Inverters Based on the Neutral-Point Current - Choi, Hye Won; Bae, Yun Jae; Lee, Kyo Beum (Journal of Electrical Engineering and Technology, 2025)
This paper proposes the lifetime extension of DC-link capacitors in three-level inverters based on the neutral-point (NP) current. High-capacity inverters require large-size capacitors to maintain robust DC-link voltage. The proposed method suppresses the ripple current of the DC-link capacitors by replacing the switching states, which are optimized for two specific modulation index regions in the linear modulation range. The reliability of the DC-link capacitors is analyzed using a capacitor lifetime model. The validation of the proposed method is supported by simulation and experimental results across various conditions.
Keywords: Capacitor lifetime; Dc-link; DC-link ripple current; Modulation indexes; Neutral points; Neutral-point clamped inverters; Neutral-point current; Point currents; Ripple currents; Three-level neutral point clamped; Three-level neutral-point clamped inverte; Capacitor lifetime; DC-link ripple current; Modulation index; Neutral-point current; Reliability; Three-level neutral-point clamped inverter